A Role for the Cytoskeleton in Heart Looping - Kersti K. Linask; Michael VanAuker (The Scientific World Journal)
Over the past 10 years, key genes involved in specification of left-right laterality pathways in the embryo have been defined. The read-out for misexpression of laterality genes is usually the direction of heart looping. The question of how dextral looping direction occurred mechanistically and how the heart tube bends remains unknown. It is becoming clear from our experiments and those of others that left-right differences in cell proliferation in the second heart field (anterior heart field) drives the dextral direction. Evidence is accumulating that the cytoskeleton is at the center of laterality, and the bending and rotational forces associated with heart looping. If laterality pathways are modulated upstream, the cytoskeleton, including nonmuscle myosin II (NMHC-II), is altered downstream within the cardiomyocytes, leading to looping abnormalities. The cytoskeleton is associated with important mechanosensing and signaling pathways in cell biology and development. The initiation of blood flow during the looping period and the inherent stresses associated with increasing volumes of blood flowing into the heart may help to potentiate the process. In recent years, the steps involved in this central and complex process of heart development that is the basis of numerous congenital heart defects are being unraveled.